PENGUATAN PENDIDIKAN KARAKTER PROFIL PELAJAR PANCASILA MELALUI MEDIA TUKAR JASA “KARTU KARAKTER PELAJAR PANCASILA” - Suci Rahayu; Arri Handayani; Dini Rakhmawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Character education is a fundamental thing that can determine the quality of education and the main foundation for students to become moral human beings in accordance with the values of Pancasila. The purpose of writing this article is to present a literature review from various sources regarding the use of character learning media so that it can help students develop their positive characters. The method used in writing this article is literature study. Currently, many students experience character loss, namely the loss of their own character, making them individuals who behave in ways that do not comply with existing rules. There are many problems with character education, especially in the school environment, and of course this is an important problem that must be resolved by presenting relevant solutions. In this case the author chose to use media in the form of character cards. From the character card media used, it can be seen that students experience an increase in character development in accordance with the dimensions of the Pancasila student profile.